How did the farmers of chhomrong improve the local paddy species? - Gurung, Om Bahadur; Gurung, Najarman; Gurung, Min Kumari; Gurung, Nauli (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Farmers from the village of Chhomrong in Nepal describe their experiences with experimental varieties of paddy rice, growing experimental varieties and selecting for specific qualities, in an initiative that started in 1993.